1990
DOI: 10.1007/bf03183924
|View full text |Cite
|
Sign up to set email alerts
|

Uses, nutritional composition, and ecogeography of four species ofPsophocarpus (fabaceae, phaseoleae) in Zaire

Abstract: In Zaire the distribution offour of the wild species in the genus Psophocarpus rangesfrom humid. evergreen. Guinea-Congolian rainforests to high altitude woodlands. dry semi-deciduous forests, and savanna. Material of Psophocarpus scandens, P. grandiflorus, P. lancifolius, P. lecomtei, and P. lancifolius (yellow-seeded form) were collectedfrom wild and naturalizedpopulations in Zaire. Various organs ofP. scandens, P. grandiflorus, and P. lancifolius are used as food sources. medicinals. and as sources oftannin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

1992
1992
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Since the 1975 publication by the US National Academy of Sciences of The Winged Bean: A High Protein Crop for the Tropics 6 , considerable effort has been focused on studying the nutritional quality and climatic and ecological tolerances of the plant 7 8 . Winged bean reportedly possesses anti-nutritional factors such as phytoglutenins, cyanogenic glycosides, tannins, lectins, flatulence factors, and saponins 9 .…”
mentioning
confidence: 99%
“…Since the 1975 publication by the US National Academy of Sciences of The Winged Bean: A High Protein Crop for the Tropics 6 , considerable effort has been focused on studying the nutritional quality and climatic and ecological tolerances of the plant 7 8 . Winged bean reportedly possesses anti-nutritional factors such as phytoglutenins, cyanogenic glycosides, tannins, lectins, flatulence factors, and saponins 9 .…”
mentioning
confidence: 99%
“…Some studies showed that seeds from E. gigas used in the preparation of traditional concoction for curing diseases in Nigeria contained essential minerals and high amount of anti-nutrient factors such as oxalate, phytate, and tannins. 4,21 These anti-nutrient factors are reduced through processing of the vegetables. Oxalate content of leaves of E. gigas is in accordance with microscopic analysis that showed abundant fragments of parenchyma with cells containing calcium oxalate crystals.…”
Section: Discussionmentioning
confidence: 99%
“…En effet, leur teneur en protéine est de 25,17±0,28 pour 100 g de matière sèche. Cette teneur est inférieure à celle de Psophocarpus scandens (36 g protéines) (Harder et al, 1990), mais supérieure à celle de Gnetum africanum (16,5 g de protéines) observée par Mialoundama (1996) et 5,95 g pour la même plante par Mbemba et al (1992). Elle est aussi élevée par rapport à celles de Pteridium centrali-africanum (0,3 g), de Dioscorea praehensilis (8,5 g), de Talinum triangulare (2 g) observées par Biloso (2008), bien que les trois légumes soient riches en eau.…”
Section: unclassified
“…Les quantités de glucides 7,78 ± 0,46 g/100 g de matière sèche dans les feuilles de T. gilletii sont inférieures à celles des feuilles de Gnetum africanum 15,53 g/100 g de MS, mais supérieures à celles de Psophocarpus scandens (Kikalakasa) 5,8 g observées par Harder et al (1990), puis 2,21 g toujours pour le P. scandens et 0,87g pour le Pteridium aquilinum (Misili) tel que observés par Mbemba et al (1989), Mbemba et Remacle (1992). Cette plante parait intéressante en formulation alimentaire dans le cadre de la prise en charge et le suivi des régimes antidiabétiques ou de gestion de la glycémie.…”
Section: Teneur En Glucidesunclassified